Issues of Unemployment in Nigeria: Effect of Real Exchange Rate and Inflation Interaction (Quarterly Journal of Econometrics Research, 2019)
The paper examines the issues regarding the effects of inflation and real exchange rate on unemployment: if change in real exchange rate and inflation reduce the level of unemployment and that inflation moderates the effect of real exchange rate on unemployment in Nigeria The author employs the Generalized Method of Moments (GMM) technique which is able to control endogeneity of variables in the study. The findings show that real exchange rate depreciation and inflation have positive impact on unemployment which in turn erodes the economic growth. Besides, the positive effect of real exchange rate depreciation on unemployment was contributed by high inflation level; the marginal effect of real exchange rate depreciation on unemployment increase with the level of inflation. This signifies that the higher the rate of inflation, the more real exchange rate depreciation spurs unemployment. Based on the findings, there is a need by the economic policy makers and authorities to establish drastic measures towards curbing high inflation level to a moderate and stable level which can stimulate a certain level of real exchange rate which in turn can urge economic growth through increase in employment opportunity.